2012
DOI: 10.1116/1.4739432
|View full text |Cite
|
Sign up to set email alerts
|

Formation of high quality nano-crystallized Ge films on quartz substrates at moderate temperature

Abstract: The hydrogenated amorphous Ge films were prepared by plasma enhanced chemical vapor deposition technique. Post-thermal annealing was applied to obtain nano-crystalline Ge (nc-Ge) films on quartz substrates. The evolution of microstructure, optical, and electrical properties was studied during the transition process from amorphous to nano-crystalline phase. It was found that the nano-crystalline Ge with size of 10–30 nm can be formed at the moderate annealing temperature (450–600 °C). Moreover, systematic inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…As shown in Figure , a very broad, low‐intensity Ge peak is observed at 277 cm −1 in the as‐deposited samples, indicating an amorphous nature of these samples. This peak can be assigned to local transverse optical (TO) phonons from random ordering of Ge atoms . As seen in the Figure , the α ‐Ge gradually crystallized with increasing annealing temperature.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As shown in Figure , a very broad, low‐intensity Ge peak is observed at 277 cm −1 in the as‐deposited samples, indicating an amorphous nature of these samples. This peak can be assigned to local transverse optical (TO) phonons from random ordering of Ge atoms . As seen in the Figure , the α ‐Ge gradually crystallized with increasing annealing temperature.…”
Section: Resultsmentioning
confidence: 89%
“…The corresponding room temperature conductivity was estimated to be ~0.9 Scm −1 . In another work, Cong Li et al prepared nc‐Ge thin films on quartz substrates deposited in plasma enhanced chemical vapor deposition system at a low substrate temperature. Their room temperature conductivity was found as 14.2 Scm −1 for the sample annealed at 600°C.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Usually, nc-Ge films can be formed by the thermal annealing (TA) of amorphous Ge (a-Ge). The a-Ge films can be crystallized when the annealing temperature is about 400 ∘ C. [9,10] In order to lower the annealing temperature, metal-induced crystallization was used and the crystallization temperature could reach as low as 165 ∘ C. [11] However, unintentional doping took place and undesired impurities existed. [12] Alternatively, laser annealing (LA), as an inexpensive and rapid processing technique, was developed.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, [9] we prepared nc-Ge films on quartz substrates by thermal annealing and studied the structural, optical, and electrical properties. It was found that nc-Ge films with sizes of 10 nm-30 nm could form at the moderate annealing temperatures (450 ∘ C-600 ∘ C), whose hole mobility could reach as high as 211 cm 2 •V −1 •s −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation